QoS support for an all IP system beyond 3G. - Robles, T. (IEEE Communications magazine)
Mobile radio systems beyond the third generation will evolve into all-IP systems, integrating Internet and mobile system advantages. The BRAIN project is developing a system architecture which combines local coverage broadband radio access systems based on HIPERLAN/2 with several wider-coverage mobile radio systems, enabling full coverage of seamless IP-based services for users in hot spot areas and on the move. End-to-end QoS provision is one of the major challenges in the design of such a system and must be supported by the application, network, and wireless access layers. This article proposes a QoS system architecture, including the terminal architecture, the IP-based access network, and the main characteristics of the enhancements to the air interface based on HIPERLAN/2 focusing on its wireless QoS support